Primary pituitary stalk mucosa-associated lymphoid tissue lymphoma: a case report and literature review - Cai, Shihao; Xiao, Juexian; Chen, Peng; Luo, Haitao; Cheng, Zujue (Frontiers in Neurology, 2023)
Background Primary extranodal mucosa-associated lymphoid tissue (MALT) lymphoma in the sellar region is a rare indolent B-cell lymphoma. Case presentation A newly diagnosed patient with MALT lymphoma originating from the pituitary stalk is reported. A space-occupying lesion in the sellar region was found in a 24 year-old man who had no clinical symptoms except for those relating to a sex hormone disorder (rising estrogen and falling androgen) identified during a pre-employment physical examination. MALT lymphoma was diagnosed pathologically. Radiotherapy and chemotherapy were proposed after surgery. However, the patient selected androgen replacement therapy only rather than chemoradiotherapy. Over the next 3 months, no visual disturbance, headache, cranial nerve abnormality, or other symptoms occurred. Conclusion Primary sellar region MALT lymphoma is an extremely rare disease. The differential diagnosis of sellar and parasellar masses should include primary sellar region MALT lymphoma. Early detection and treatment of this lymphoma can effectively improve the prognosis.